Exploring the Crosstalk between Inflammation and Epithelial-Mesenchymal Transition in Cancer - Indranil Chattopadhyay; Rangarao Ambati; Rohit Gundamaraju (Mediators of Inflammation)
Tumor cells undergo invasion and metastasis through epithelial-to-mesenchymal cell transition (EMT) by activation of alterations in extracellular matrix (ECM) protein-encoding genes, enzymes responsible for the breakdown of ECM, and activation of genes that drive the transformation of the epithelial cell to the mesenchymal type. Inflammatory cytokines such as TGFβ, TNFα, IL-1, IL-6, and IL-8 activate transcription factors such as Smads, NF-κB, STAT3, Snail, Twist, and Zeb that drive EMT. EMT drives primary tumors to metastasize in different parts of the body. T and B cells, dendritic cells (DCs), and tumor-associated macrophages (TAMs) which are present in the tumor microenvironment induce EMT. The current review elucidates the interaction between EMT tumor cells and immune cells under the microenvironment. Such complex interactions provide a better understanding of tumor angiogenesis and metastasis and in defining the aggressiveness of the primary tumors. Anti-inflammatory molecules in this context may open new therapeutic options for the better treatment of tumor progression. Targeting EMT and the related mechanisms by utilizing natural compounds may be an important and safe therapeutic alternative in the treatment of tumor growth.